HUBUNGAN ANTARA BEBAN KERJA DAN STRES KERJA PADA KARYAWAN ADMINISTRASI DI UNIVERSITAS X - Sakti, Eka Wulan (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
In the implementation of the lecture is not only determined the success of the role of faculty and students only. But employees also have pernaan important in the ongoing success of the learning process indirectly. Conditions of employees becomes very important, it is necessary to do the job conducive conditions. Job stress is a phenomenon that is common in todays working life. Job stress is itself a response to a stimulus that appeared with the pressure and demands of the environment that exceeds the capacity of the individual as an employee. Job stress can impact both physically and psychologically. The workload is one of the factors that affect the appearance of job stress. If the workload exceeds the capacity of the workers it will affect a persons ability to increased work stress on the individual. This study aimed to determine the relationship of the workload with work stress on university administration employees X. The method used in the present study using quantitative methods. Subject selection techniques using the total population, in which the amount of the whole subject as many as 62 people of all employee population. Data were collected using three questionnaires that measured using a Likert scale, namely a questionnaire containing about workload and job stress. The results of this study indicate that there is a relationship between workload and job stress in university administration employees X (r = 0.268; p = 0.018). The researchers also looked at the effect of each aspect workload and job stress effect on each of its aspects. It is important for research subjects to be having a positive stress transfer by using meditation and can set the time in the execution of tasks. suggestions for research subjects is important to have a positive stress transfer by not leaving the job. In addition, it is important to set the time on the task at hand.